Analisis Attitude-Value Pembelajaran IPS Terhadap Sikap Peduli Sosial Siswa - Khoirul Huda; Gogot Sugito (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The industrial era 4.0 that is happening now has had a lot of influence in various aspects of life and has caused social problems. One of the subjects that is a means of cultivating social attitudes is the subject of Social Sciences (IPS). The purpose of this study was to analyze the effect of Attitude-Value of Social Studies Learning on Students' Social Care Attitudes at SMK Plus Umar Zahid Semelo. With an ex-post facto model and a quantitative approach with a population of students from class XII-A to class XII-E SMK Plus Umar Zahid Semelo, a total of 75 students. Variable measurements were carried out using a Likert scale. Data were collected through literature, observation and questionnaires and by means of statistical mortgage analysis and simple regression analysis with the hypothesis test Rsquare, f and t. The results obtained are the influence of the Attitude-Value (av) approach variable in the high category. In the Social Care Attitude (SPS) variable, with an attitude of mutual help, tolerance, tolerance, social action and noble character, it affects 75 students with moderate levels and the Attitude-Value approach has a significant effect simultaneously or partially in increasing social care attitudes learners.